Spinal Tuberculosis: Spectrum of MR Findings with Laboratory Evaluation - Sutanto, Ratna; Pratama, Teodorus; Koesbandono, Koesbandono; Chandra, Yohanes (Indonesian Journal of Medicine, 2024)
Background: Tuberculosis infections are endemic diseases in Asian countries. Although the incidence is rare, tuberculous spondylitis manifests as a severe and life-threatening disease. This study aims to correlate the abnormal result of erythrocyte sedimentation rate (ESR) and magnetic resonance (MR) imaging findings. Subjects and Method: MR imaging of 60 patients with characteristics of spinal tuberculosis in 4-year 5 month period (January 2019 – May 2023) from Siloam Lippo Village is retrospectively analyzed and reviewed. Data were collected from Infinitt PACS and analyzed by SPSS. Dependent variables in this study are clinical suspicion for tuberculosis infection, erythrocyte sedimentation rate (ESR), and tuberculosis infection in different organs. Meanwhile, the independent variables in this study are multilevel vertebral involvement, multilevel disc involvement, abscess formation, and myelopathy. Results: Association with elevated ESR (erytrocyte sedymentation rate) are seen in 11 out of 31 patients aged >40 (OR=0.45; CI 95%= 0.16 to 1.26; p=0.120), 19 out of 37 patients with clinically suspected for tuberculosis infection (OR=1.98; CI 95% 0.68 to 5.78; p=0.210); 27 out of 55 patients with multilevel vertebral body involvement (OR=0.8; CI 95%= 0.12 to 5.17); p=1); 13 out of 30 patients with intervertebral disc involvement (OR=0.87; CI 95% 0.32 –to2.42); p=0.8); 20 out of 50 patients with abscess formation(OR=0.29; CI 95%=0.66 to 1.24; p=0.08); 5 out of 12 patients with tuberculosis infection on other organs(OR=0.84; CI 95%=0.24 – 3.04; p=0.8); and 5 out of 6 patients with myelopathy(OR=7.3; CI95%=0.79 TO 66.6; p=0.04). Conclusion: MR has an important role in detecting extrapulmonary tuberculosis lesions, especially in the spine. Elevated ESR results play important roles for physicians in identifying patients with the possibility of spondylitis TB.